Determination and Testing the Domination Numbers of Tadpole Graph, Book Graph and Stacked Book Graph Using MATLAB (College of Basic Education Research Journal, 2011)
A set is said to be dominating set of G if for everythereexistsavertex such that .Theminimumcardinality of vertices among dominating set of G is called thedominationnumberofGdenotedby .WeinvestigatethedominationnumberofTadpolegraph,BookgraphandStackedBookgraph.Alsowetestour theoretical results incomputerbyintroducing amatlab procedure to find the domination number ,dominating set S and draw this graph that illustrates the vertices ofdominationthisgraphs.Itisprovedthat
Keywords: Dominating set; Domination number; Tadpole graph; Book graph; stackedgraph